Effects of Lutjanus erythropterus Protein on Depression-like Behavior and Gut Microbiota in Stressed Juvenile Mice - Jinjin Luo; Chen Wang; Weichang Ye; Ruiyang He; Ling Huang; Zhijia Fang; Qi Deng; Mei Qiu; Lijun Sun; Ravi Gooneratne (Foods)
Lutjanus erythropterus protein (Lep) exhibits anti-inflammatory effects, but its antidepressant activity is unknown. This study used a 44-day chronic unpredictable mild stress (CUMS) model to determine whether Lep has a beneficial effect through the gut–brain axis in 3-week-old male C57BL/6 mice. Gavaging with Lep solution alleviated the depression-like behavior and anxiety symptoms in CUMS growing mice. Administration of Lep decreased serum IL-1β, IL-2, IL-6, and TNF-α levels and restored colonic mucosal damage. In addition, Lep improved the disturbance of 5-hydroxytryptamine (5-HT) secretion in the gut–brain axis. Pearson analysis revealed that gut short-chain fatty acid (SCFAs) concentration significantly (p < 0.05) correlated with mucosal damage scores and the depression-like behavior index. Lep was able to prevent the gut SCFA enrichment. Lep upregulated gut Muribaculaceae and downregulated SCFA-producing bacteria by replenishing deficient amino acid (AA) (tryptophan, alanine, aspartate, glutamate) and decreased (p < 0.01) the gene abundance of the AA metabolism pathway of SCFA-producing bacteria, thereby preventing gut SCFA enrichment and alleviating associated depression-like behavior. These findings indicate that Lep could attenuate depression in CUMS juvenile mice via the gut microbiota-SCFA–brain axis.